Recursos didácticos en el área de lengua y literatura - Torres Morales, María Mercedes (2016)
Teaching resources are necessary tools that serve as support in the development of the theoretical content, these help to differentiate the content and methods used in the educational process, in order to promote innovations that help transmit knowledge. By implementing teaching resources in educational institutions it is achieved facilitate the process of learning of Language and Literature. At school Rio San Pablo has been observed that a comprehensive reading and proper writing is not applied in the teaching-learning students in the seventh year of basic education in the area of Language and Literature, learners do not analyze content text and to some extent take it in a boring way, this establishes that most of the problems in learning is due to the traditional way of teaching and lack of teaching resources for reading comprehension by teachers to promote development through learning techniques in students. Reading and writing are cultural practices; ie activities carried out by groups with specific purposes in specific contexts. Teachers poorly prepared teaching resources for mediation of content in the area of Language and Literature, for this reason no significant learning that encourages to be that students are active in the development of language skills develop listening, speaking, reading and write excellently. For the realization of this project has been taken as a reference performing a diagnosis through observation students and surveys of the educational community made up of 31 students, 31 parents and 7 teachers, it is for this reason that it has been evident that the lack of updating and use of educational resources by some teachers are factors that affect the process (teaching - learning), resulting in the school disinterest and poor academic performance. For this it is necessary to implement new teaching resources to date in the area of Language and Literature, according to reality, through a methodological guide and socialization workshops arousing student interest in reading and improve their reasoning (critical-analytical) and writing.